Changes in the burden and underlying causes of rheumatic heart disease in children and youths, 1990–2021: an analysis of the Global Burden of Disease Study 2021 - Li, Chang; Gao, Liuming; Wang, Yanggan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundUnderstanding the temporal evolutions in the burden of rheumatic heart disease (RHD) in children and youths is vital for devising effective and targeted preventative measures. Our objective was to deliver an accurate and thorough assessment of the prevalence, incidence and deaths of RHD in children and youths aged 5–19 years at global, regional, and national scales.MethodsWe utilized the analytical tools provided by the Global Burden of Disease and Injuries (GBD) 2021 to assess the impact of RHD on the population of children and youths aged 5–19 years. This analysis considered factors such as sex, age, region, and encompassed 204 countries and territories spanning the years 1990–2021.ResultsThe global age-standardized incidence rate (ASIR, per 100,000 population) of RHD in children and youths notably increased from 77.98 (95% confidence interval: 51.93, 110.15) in 1990 to 93.96 (62.05, 134) in 2021. Similarly, the age-standardized prevalence rate also significantly increased from 498.49 (340.79, 686.31) to 588.46 (396.8, 816.79), with an estimated annual percentage change (EAPC) of 0.42% (0.4%, 0.44%). In contrast, the global age-standardized mortality rate (ASDR, per 100,000 population) declined moderately from 1.23 (1.020, 19.89) in 1990 to 0.52 (0.45, 0.58) in 2021, with an EAPC of −2.71% (−2.9%, −2.53%). When analyzed by sociodemographic index (SDI), regions with low and low-middle SDI exhibited a greater RHD burden compared to those with high and high-middle SDI. Geographically, Sub-Saharan Africa and South Asia experienced a higher prevalence of RHD than other regions. Additionally, gender disparities were observed: women exhibited a greater prevalence of RHD, while men demonstrated higher mortality rates associated with the condition. These trends highlight the persistent global burden of RHD, particularly in lower-resource settings and among specific demographic groups.ConclusionsThe global burden of RHD among children and adolescents remained significant in 2021. The burden of RHD differs based on factors such as age, gender, SDI, region and country. RHD in children and youths is predominantly preventable, highlighting the need for increased focus on the targeted execution of efficient primary prevention strategies and the enhancement of healthcare systems that cater to young individuals.